On the development of inexpensive speed and position tracking system for swimming - Trangbaek, S.; Rasmussen, C.; Bull Andersen, T. (Sports Technology, 2015)
A semi-automated tracking system was developed for the analysis of swimming, using cameras, an LED diode marker, and a red swim cap. Four experienced young swimmers were equipped with a marker and a swim cap and their position and speed was tracked throughout above water and underwater swimming sequences, using post image processing in MATLAB®. The results showed that this technique can be used to track a swimmer both under and above water, and identify speed fluctuations.